Effect of hydrothermal process for inorganic alumina sol on crystal structure of alumina gel*. Issue 3 (1st September 2016) - Yamamura, K.; Hama, M.; Kobayashi, Y.; Yasuda, Y.; Morita, T.
Abstract: This paper reports the effect of a hydrothermal process for alumina sol on the crystal structure of alumina gel derived from hydrothermally treated alumina sol to help push forward the development of low temperature synthesis of α-Al2 O3 . White precipitate of aluminum hydroxide was prepared with a homogeneous precipitation method using aluminum nitrate and urea in aqueous solution. The obtained aluminum hydroxide precipitate was peptized by using acetic acid at room temperature, which resulted in the production of a transparent alumina sol. The alumina sol was treated with a hydrothermal process and transformed into an alumina gel film by drying at room temperature. Crystallization of the alumina gel to α-Al2 O3 with 900 °C annealing was dominant for a hydrothermal temperature of 100 °C and a hydrothermal time of 60 min, as production of diaspore-like species was promoted with the hydrothermal temperature and time. Excess treatments with hydrothermal processes at higher hydrothermal temperature for longer hydrothermal time prevented the alumina gel from being crystallized to α-Al2 O3 because the excess hydrothermal treatments promoted production of boehmite.